Inflammation in Sjögren's syndrome: Cause or consequence? - Ana Raquel Rodrigues; Raquel Soares (Taylor & Francis Group, 2017)
Sjögren's syndrome (SS) is an autoimmune disease most commonly characterized by ocular and oral dryness. Despite the high prevalence of SS, generation and perpetuation of this disease is still unclear in many aspects. Inflammation, nonetheless, seems to play a central role in this pathology especially in the form of Th-1, Th-2 and Th-17 cytokines release within different aspects, concentrations and connections involved in the maintenance of the syndrome. Moreover, the chronically created pro-inflammatory environment appears to promote glandular atrophy and irreparable architectural modifications. The establishment of germinal centers (GC) in SS are considered the main reason for the 16-times increased probability of lymphoproliferative disease development in these patients. SS is also interconnected with numerous others auto-inflammatory and autoimmune diseases, many of them representing the first clear sign of a dysregulated immune system. Despite the recent advances, treatment options are still insufficient. This overview aims to better elucidate this local and systemic disease, which can be of vital use not only for SS but also to other rheumatic pathological conditions.